Contact dermatitis in children - Marsili Chiara; Martelli Alberto; Pigatto Paolo; Fiocchi Alessandro (BMC, 2010)
Abstract Contact dermatitis in pediatric population is a common but (previously) under recognized disease. It is usually divided into the allergic and the irritant forms. The diagnosis is usually obtained with the patch test technique after conducting a thorough medical history and careful physical examination but patch testing in infants may be particularly difficult, and false-positive reactions may occur. This study also provides an overview of the most common allergens in pediatric population and discusses various therapeutic modalities.